PENGARUH PEMBIAYAAN SYARIAH TERHADAP PROFITABILITAS PADA BANK UMUM SYARIAH DI INDONESIA TAHUN 2019-202 - Helmiati, Helmiati; Kasmawati, Kasmawati; Putri, Febriani (Ensiklopedia of Journal, 2025)
This study aims to examine the influence of murabahah, mudharabah and musyarakah financing on the profitability of Sharia Commercial Banks in Indonesia in 2019-2023. Samples were taken using a purposive sampling method, totaling 10 companies. Based on the simultaneous test results Murabahah, Mudharabah and Musyarakah have a significant effect on Profitability. While partially Murabahah, Mudharabah and Musyarakah financing also have a significant effect on profitability. The contribution of the independent variable to the dependent variable is 54,7% and the remaining 45,3% is influenced by other variables not included in this research. Hypothesis testing was carried out using multiple linear regression using SPSS 25.